A Review of The Potential Marsilea crenata Presl. Leaves to Prevent Osteoporosis in Menopausal Women - Novita Dwi Astutik; Meike Tiya Kusuma; Jamila; Sandiena Mahesa Adzra (Journal of Research in Midwifery and Healthcare, 2025)
Women going through menopause often experience osteoporosis.One preventive measure comes from herbal plants, especially thosecontaining isoflavones like Marsilea crenata Presl. leaves. This plantwas chosen because it has been proven as antioxidant, antiinflammatory,and estrogenic effects that similar to naturalhormones. The aim of this study is to investigate the potential ofMarsilea crenata Presl. leaves as herbal therapy for preventingosteoporosis. The study employs a literature review approachcollected from various scientific databases such as Science Direct,PubMed, and Google Scholar. Articles were selected by exclusionand inclusion criteria. The results indicate that isoflavones fromMarsilea crenata Presl. leaves interact with estrogen receptors,helping to maintain balance between osteoblast and osteoclastactivity and reducing bone resorption. Based on in vitro and in vivostudies, the isoflavones in Marsilea crenata Presl. leaves includedaidzein, genistein, biochanin A, and formononetin. In addition, theantioxidant and anti-inflammatory properties of Marsilea crenataPresl. leaves extract can enhance its therapeutic potential. Acomprehensive study explains the oral consumption of Marsileacrenata Presl. leaves extract in postmenopausal women can increasebone density and alleviate vasomotor symptoms